Pengaruh Model Somatic Auditory Visualization Intellectual (SAVI) Berbantuan Media Flashcard Terhadap Kemampuan Numerasi Peserta Didik Kelas III Sekolah Dasar - Pratiwi, Anisa Dian; Rapani, Rapani; Hermawan, Jody Setya; Nurwahidin, Muhammad (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2025)
This research is motivated by the low numeracy skills of third-grade students at SD Negeri 1 Metro Barat. This study aimed to determine the effect of the Somatic, Auditory, Visualization, Intellectual (SAVI) learning model assisted by Flashcard media on the numeracy skills of third-grade students at SD Negeri 1 Metro Barat. This research employed a quasi-experimental designwith apre-test-post-test control group design. The population of this study involved all 41 students, and  thesample consisted of 20 students. Data collection techniques includedtests (pre-test and post-test) to measure numeracy skills, observation to examine interactions and learning processes, and interviews to gather more in-depth information from teachers or students regarding their learning experiences. Data analysis was conducted using a simple linear regression test to determine the significance of the effect of the SAVI model assisted by Flashcards on students' numeracy skills. Theresults indicated a significant effect of applying the SAVI model assisted by Flashcard media on students' numeracy skills, with a significance value (2-tailed) of 0.000 0,05.